Design, analysis and innovation in variable radius active screw in-pipe drive mechanisms. (3rd May 2017) - Ren, Tao; Liu, Qingyou; Li, Yujia; Chen, Yonghua
Modern pipelines are often very long, having bends, branches and even variable diameters. Moving inside such pipelines to perform certain tasks has not been easy. There are various design concepts for traction inside a pipe. Screw drive is one of the concepts for in-pipe traction. This article presents a general description and analysis of available screw drives that have been used for in-pipe drives. The main focus is on the characteristic analysis of a novel variable radius screw drive mechanism that is proposed by the authors. The proposed mechanism is a two-stage planetary gearing system driven by a single motor. Major parameters of the mechanism, including helical angle, pitch and forward velocity, are derived. Furthermore, by conducting a force analysis, it is found that the proposed mechanism has much larger thrust force compared with that of the existing screw drive mechanism. A larger thrust force means that the proposed mechanism can carry more devices, thus perform more tasks inside pipes. To demonstrate the effectiveness of the proposed mechanism, thrust force measurement experiments have been conducted.